The Study of Unpredictable Situations of Private Higher Education Institutions with VUCA Concept - Jairtalawanich, Suwimol; Sathirakul Tachaphahapong, Sirichan; Polsaram , Pansak (Dusit Thani College Journal, 2023)
The research on the unpredictable situation of private higher education institutions using the VUCA concept aims to study the current situation and problems of managing private higher education institutions to cope with unpredictable situations and analyze unpredictable situations in managing private higher education institutions using the VUCA concept, which consists of Volatility, Uncertainty, Complexity, and Ambiguity. The research methodology used was qualitative research by studying documents, interviewing high-level and mid-level executives, and 24 education experts. Therefore, it can be concluded that the current situation is volatile due to both local events and digital disruption. The complexity arises from the students’ learning preferences, which cannot be controlled. The ambiguity arises from the unclear government policies supporting private higher education institutions, which are crucial for their survival. The challenges that private higher education institutions must face include academic volatility, fluctuating student demand and behavior, uncertain rules and policies, complex understanding of students, and ambiguous perceptions of employees. In terms of research, the focus should be on practical and community-based research to ensure its relevance and impact. However, there is still a lack of clarity in national research funding and policy. Additionally, there is a complex regulatory environment in each institution that supports research. The fluctuation in demand for academic services, uncertainty in student income, complexity in strategic planning and policy of the government, requires academic services to be more tailored to the needs of entrepreneurs and communities. The most important thing for private higher education institutions is to have a survival plan and place more importance on innovative ways to attract students. Continuous self-development and adaptation to the situation are necessary.